The Influence of Digital Literacy on Digital Entrepreneurial Intention: Building Entrepreneurial Resilience among Business Students in the Digital Transformation Era - Budiman; Zahra, Puti (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The rapid advancement of digital technology has transformed entrepreneurial ecosystems, demanding individuals to develop strong digital competencies and adaptability. This study aims to examine the influence of digital literacy on digital entrepreneurial intention as a means to build entrepreneurial resilience in the digital transformation era. The research was conducted with 120 students from the Faculty of Economics and Business (FEB) in Bandung, Indonesia, who were considered to have basic exposure to entrepreneurship and digital tools. The study employed a quantitative descriptive approach with simple linear regression analysis using SPSS version 26. Classical assumption tests, including the Kolmogorov–Smirnov test for normality and the Glejser test for heteroscedasticity, were applied to ensure model validity. The normality test showed a significance value of 0.200 (>0.05), indicating that the residuals were normally distributed. The heteroscedasticity test yielded a p-value of 0.055 (>0.05), indicating that the model was free of heteroscedasticity. The regression results demonstrated that digital literacy has a positive and significant effect on digital entrepreneurial intention, with a standardized coefficient (β) of 0.601 and a significance level of 0.000. The model yielded an R-square of 0.361, suggesting that digital literacy explains 36.1% of the variance in digital entrepreneurial intention. These findings highlight the critical role of digital literacy in fostering students’ readiness to pursue digital entrepreneurship and in strengthening entrepreneurial resilience amid the ongoing digital transformation.